Experiential marketing: bridging the gap between value creation to customers and value capture by firms - Paixão, João António Pereira (2021)
An already voluminous literature addressing the value of marketing to the firm has, until now, fallen short of expectations. In a context in which marketers have increasingly been challenged to prove their worth, the scholarly attempts to demonstrate the value of marketing to the firm have stumbled to reach unquestionable results. Part of the problem may lie in the lengthy and twisted chain of effects from marketing actions to marketing performance outcomes. Between inputs and outputs lie numerous uncontrollable and often confounding external factors, such as the actions of customers, competitors, and other market agents. The problematic operationalization of such complex market structures impelled researchers to analyze fractions of this web of effects rather than attempting to study overarching conceptual models in full. Prior empirical research has typically considered either the impact of marketing actions in the marketplace or the consequences to the firm of the behaviors of customers and rivals. There is still a gap in the literature of an all-encompassing end-to-end demonstration of how specific marketing inputs can drive specific marketing outputs unequivocally contributing to organizational performance. This thesis addresses the issue of marketing as a value-capturing corporate function through its determinant role in managing value-creating exchanges with customers in the marketplace while hindering competitors from appropriating it. Our research suggests that experiential marketing may bridge the gap between value creation to the customer and value capture by the firm. In particular, our findings show that marketing-crafted valuecreating online shopping experiences may predict value-capturing marketing performance outcomes with the mediation of superior customer-level marketing performance. Thus, our results suggest that experiential marketing may offer an opportunity to bridge the gap between "give and take," value creation and value capture, and demonstrate how relevant the contribution of marketing to the firm's value rising can be.